The Effect of Institutional Ownership, Company Diversification, and Profitability on Company Value in Manufacturing Companies Listed on The Indonesia Stock Exchange - Bahri Lifaldi; Ewing Yuvisa Ibrani; Lia Uzliawati (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to analyze the effect of institutional ownership, company diversification, and profitability as independent variables on firm value as the dependent variable. In addition, this study also uses company size as a control variable. This research is a causative research. The population of this study are all manufacturing companies listed on the IDX in 2014-2018. This research was conducted using a sampling technique based on purposive sampling technique, so a total sample of 206 was obtained. The data used in this research is secondary data obtained from www.idx.co.id and IDNFinance. The analysis technique used is multiple regression analysis. To test the hypothesis using the statistical t test with an Î± level of 0.05. The results of this study indicate that: (1) institutional ownership has a positive effect on the value of manufacturing companies with sig = 0.048, 0.043 (< 0.05), (2) company diversification (number of segments) has a positive effect on the value of manufacturing companies with sig = 0.029 (<0.05), (3) company diversification (HERFsales) has a positive effect on the value of manufacturing companies with sig = 0.077 (> 0.05), (4) profitability has a positive effect on the value of manufacturing companies with sig = 0.027, 0.041 (< 0.05), (5) firm size has a positive effect on firm value with sig = 0.000, 0.000 (< 0.05).